Cardiac resynchronization therapy is associated with a reduction in ICD therapies as it improves ventricular function. Issue 6 (5th June 2018) - Galve, Enrique; Oristrell, Gerard; Acosta, Gabriel; Ribera‐Solé, Aida; Moya‐Mitjans, Àngel; Ferreira‐González, Ignacio; Pérez‐Rodon, Jordi; García‐Dorado, David
Abstract : Background: Repeated implantable cardioverter‐defibrillator (ICD) therapies cause myocardial damage and, thus, an increased risk of arrhythmias and mortality. Hypothesis: Cardiac resynchronization therapy–defibrillator (CRT‐D) reduces the number of appropriate therapies in patients with left ventricular dysfunction (left ventricular ejection fraction [LVEF] <50%). Methods: The retrospective study involved 175 consecutive patients (mean age, 64.6 ±10.4 years; 86.9% males) with reduced LVEF of 27.9% ±7.6% treated with an ICD (56.6%) or CRT‐D (43.4%), according to standard indications, between January 2009 and July 2014. Devices were placed for either primary (54.3%) or secondary prevention (45.7%). Mean follow‐up was 2.5 ±1.5 years. Predictors of first appropriate therapy were assessed using Cox regression analysis. Results: Forty‐four (25.1%) patients received ≥1 appropriate therapy. Although patients treated with CRT‐D had lower LVEF and poorer New York Heart Association class, CRT‐D patients with LVEF improvement >35% at the end of follow‐up had a significantly lower risk of receiving a first appropriate therapy relative to those with an ICD (adjusted hazard ratio: 0.24, 95% confidence interval: 0.07–0.83, P  = 0.025), independently of ischemic cardiomyopathy, baseline LVEF, and secondary prevention. There were no differences in mortality between the ICD and the CRT‐D groups. Conclusions: Although patients receiving CRT‐D had a worse clinical profile, they received fewer device therapies in comparison with those receiving an ICD. This reduction is associated with a significant improvement in LVEF.